Sociological aspects of video games in childhood culture - Loayza, Jerjes (2023)
In a child's life, there are numerous influences that are projected on him, both in his primary and secondary socialization. Indeed, the roles and functions that he gradually acquires in the family and, later, in school and in the neighborhood, play a fundamental role in the structuring of his subjectivity and his intersubjectivity in relation to his environment. It is a reciprocal relationship between him and his context, where he must strengthen his security for the constitution of the self, while he will contribute with his creativity and commitment to the social space where he immerses himself with full intention, focusing on his identification and constant integration. Childhood is crossed by a performativity that will repeat a dichotomous process around the social differentiation of the sexes that both the boy and the girl will internalize under the label of normality, becoming perennialized until adulthood, where the individual is amalgamated to a series of rituals and convergences of diverse nature. It is worth noting that, according to the context and society to which we are referring, this kind of performativity will have different paths and results in the person. The Latin American case, for example, and more particularly the Peruvian case, reflects the way in which a series of behaviors are inhibited under the dichotomy of the sexes applied to gender identity,